2011
DOI: 10.3389/fpsyg.2011.00207
|View full text |Cite
|
Sign up to set email alerts
|

Unable to Conform, Unwilling to Rebel? Youth, Culture, and Motivation in Globalizing Japan

Abstract: This paper investigates the effects of globalization on Japanese young adults from sociological and psychological perspectives. While Japan’s socio-economic institutions have shown mainly resistant (or “hot”) reactions to globalization, individual-level adaptations remain oriented toward conformity to dominant life expectations, which remain largely unchanged, despite decreasing rewards. However, a socially withdrawn sub-group (the so-called hikikomori) appears to be unable to conform yet is also unwilling to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 38 publications
1
67
0
5
Order By: Relevance
“…Individualism has spread throughout Japan due to globalization (Toivonen, Norasakkunkit, & Uchida, 2011), both at the personal and at the macro levels. At the personal level, for instance, average family size has decreased, the divorce rate has increased, and the importance of independence during child socialization has increased.…”
Section: Wellbeing and Deviation From The Cultural Mainstreammentioning
confidence: 99%
“…Individualism has spread throughout Japan due to globalization (Toivonen, Norasakkunkit, & Uchida, 2011), both at the personal and at the macro levels. At the personal level, for instance, average family size has decreased, the divorce rate has increased, and the importance of independence during child socialization has increased.…”
Section: Wellbeing and Deviation From The Cultural Mainstreammentioning
confidence: 99%
“…Since the Japanese government's guidelines did not specify the social relationships of socially withdrawn youths, among the five articles, three considered that Borovoy (2008) Expert opinion Furlong (2008) Expert opinion Wilson (2010) Expert opinion Teo and Gaw (2010) Review Teo (2010) Clinical review Toivonen et al (2011) Expert opinion Rosenthal and Zimmerman (2012) Expert opinion Suwa and Suzuki (2013) Expert opinion Heinze and Thomas (2014) Expert opinion Chan and Lo (2014c) Review Baek (2014) Expert opinion SAD: social anxiety disorder. The table summarizes the included articles by study type (qualitative study, quantitative study and others) and years of study (2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014).…”
Section: Operational Definitionsmentioning
confidence: 99%
“…Studies have shown that Japanese adults score higher on this scale compared to Japanese students, European American students (Hitokoto & Uchida, 2014) and European American adults (Hitokoto, in prep). These results may point to the fact that those living in a mainstream interdependent cultural context such as the mainstream Japanese working context (Toivonen, Norasakkunkit, & Uchida, 2011) are likely to show high levels of interdependent happiness. We can extend these findings by replicating the high score in other interdependent cultural contexts.…”
Section: Research Questionmentioning
confidence: 89%